1990
DOI: 10.1007/bf00170924
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline serine protease produced from citric acid by Bacillus alcalophilus subsp. halodurans KP 1239

Abstract: Maximum production of alkaline serine protease by Bacillus alcalophilus subsp. halodurans KP 1239 was achieved after 24 h cultivation, at an initial pH of 7.6, on a medium containing 1.0% sodium citrate, 0.3% yeast extract, and 0.3% KH2PO4. The enzyme was purified to crystalline form from culture broth. The enzyme was most active at 60 degrees C and at pH 11.5. The molecular weight, isoelectric point and sedimentation coefficient in water at 20 degrees C were estimated as 29,000, 8.8 and 3.3S, respectively. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…The K m value of the purified halophilic protease towards casein was 523 µg mL −1 . This result is comparable to the results of Juhasz and Skarka (1990), Takii et al (1990) and Mesbah and Wiegel (2014), who reported that proteases with low K m values (400 and 1300 µg mL −1 ) towards casein substrate were produced by Bacillus alkalophilus, Brevibacterium linens and Alkalibacillus sp. NM-Fa4, respectively.…”
Section: Living-cell Count (Cells/ml)supporting
confidence: 94%
“…The K m value of the purified halophilic protease towards casein was 523 µg mL −1 . This result is comparable to the results of Juhasz and Skarka (1990), Takii et al (1990) and Mesbah and Wiegel (2014), who reported that proteases with low K m values (400 and 1300 µg mL −1 ) towards casein substrate were produced by Bacillus alkalophilus, Brevibacterium linens and Alkalibacillus sp. NM-Fa4, respectively.…”
Section: Living-cell Count (Cells/ml)supporting
confidence: 94%
“…Similar studies on growth kinetics were also carried out with Bacillus sp. and other haloalkaliphilic organisms (Takii et al 1990;Ferrero et al 1996;Studdert et al 1997). In case of Aspergillus flavus, maximum enzyme production was obtained during the stationary phase.…”
Section: Resultsmentioning
confidence: 96%
“…Merkel and Sipos [42] reported a protease from marine Vibrio, the temperature optima of which shifted from 40 to 50 8C in presence of 10 À3 M Ca 2+ ion. Better thermostability and enhancement of activity of our protease in the presence of Ca 2+ may possibly be a general effect of stabilizing as well as increasing the activity of serine proteases, mostly derived from Bacillus species [43][44][45][46][47]. As regards inhibition of protease activity by heavy metals, a review of literature shows that certain bacterial serine proteases are repressed by Zn 2+ , Hg 2+ and Cu 2+ while others are not.…”
Section: Discussionmentioning
confidence: 99%